If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + -4) = 3(y + 5) Reorder the terms: 2(-4 + 2y) = 3(y + 5) (-4 * 2 + 2y * 2) = 3(y + 5) (-8 + 4y) = 3(y + 5) Reorder the terms: -8 + 4y = 3(5 + y) -8 + 4y = (5 * 3 + y * 3) -8 + 4y = (15 + 3y) Solving -8 + 4y = 15 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -8 + 4y + -3y = 15 + 3y + -3y Combine like terms: 4y + -3y = 1y -8 + 1y = 15 + 3y + -3y Combine like terms: 3y + -3y = 0 -8 + 1y = 15 + 0 -8 + 1y = 15 Add '8' to each side of the equation. -8 + 8 + 1y = 15 + 8 Combine like terms: -8 + 8 = 0 0 + 1y = 15 + 8 1y = 15 + 8 Combine like terms: 15 + 8 = 23 1y = 23 Divide each side by '1'. y = 23 Simplifying y = 23
| 0.4(x-9)=20 | | 1.29*x=5 | | 3x+25=17x | | X^3+9X^2+20X=0 | | X^3+2X^2-2X-4=0 | | (x+5)(4x-3)=0 | | X^4-X^3+5X^2-5X=0 | | 3y^2=-5y-2 | | 418=-22 | | 8x^3=2x | | 0+-5n=2n | | -10p+99=12 | | 9a=4b | | x*5=135 | | -48=8e | | 4x-30=50+2x | | 5o-2.6=27.4 | | 2x+90=180 | | S+6=-3 | | T-(-5)=12 | | d+3=14 | | N-2=10 | | 8x^2+7b^2= | | -8u-2=14 | | 3c+4=16 | | x^3+6*x-8=0 | | (6-11)x=14+x | | 6-11x=14+x | | 3m+6=3.5m-1 | | 3(x+11)=11x-19 | | x^8-7x^7-3x^6= | | (4x+1)(2x^2+x+1)= |